Improved UV Spectrophotometric Method for Precise, Efficient and Selective Determination of Dexamethasone in Pharmaceutical Dosage Forms - Sversut, Rúbia Adrieli; Vieira, James Cabral; Rosa, Aline Marques; Singh, Anil Kumar; do Amaral, Marcos Serrou; Kassab, Nájla Mohamad (Orbital: The Electronic Journal of Chemistry, 2015)
An improved UV spectrophotometric method has been developed and validated for precise, efficient and selective determination of dexamethasone in tablets and capsules. The quantitative analyses were carried out using ethanol/water (2:1 v/v) as background electrolyte and UV detection was carried out at 240 nm. The calibration curve was linear over a concentration range from 4.0 to 40.0 µg mL-1. The average recovery was 97.60 ± 1.06% for tablets and 96.64 ±0.87% for capsules. The limit of detection and limit of quantification were 0.63 and 1.90 µg mL-1, respectively. The method was validated according to ICH guidelines and the acceptance criteria for accuracy, precision, linearity, specificity and system suitability were met. The results obtained with proposed method confirm improved performance over other methods found in the literature.DOI: http://dx.doi.org/10.17807/orbital.v7i1.630